2018
DOI: 10.1038/s41598-018-30379-9
|View full text |Cite
|
Sign up to set email alerts
|

The molecular chaperon AKR2A increases the mulberry chilling-tolerant capacity by maintaining SOD activity and unsaturated fatty acids composition

Abstract: Chilling is common in nature and can damage most plant species, particularly young leaves and buds. Mulberry (Morus spp.) is an economically important food source for the domesticated silkworm (Bombyx mori). However, weather and climatic extremes, such as “late spring coldness”, seriously damage mulberry buds and young leaves. The molecular mechanism involved in the differing mulberry chilling tolerance is unclear. In the present study, we found that mSOD1, mFADII, and mKCS1 interacted with mAKR2A and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…We conjecture that the intricate regulatory network enmeshing MaCDSP32 is responsible for the rapid wilting of the transgenic lines during severe water deficit and their maintenance of the minimum water consumption, which allows their survival under drought conditions. The SOD enzyme is the main site of the conversion of superfluous O 2 − via its disproportionation in the chloroplast (Chen et al, 2018). Based on the results obtained for SOD activity and O 2 − production demonstrate that MaCDSP32 plays a key role in the regulation of ROS homeostasis by particularly targeting the SOD enzyme.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We conjecture that the intricate regulatory network enmeshing MaCDSP32 is responsible for the rapid wilting of the transgenic lines during severe water deficit and their maintenance of the minimum water consumption, which allows their survival under drought conditions. The SOD enzyme is the main site of the conversion of superfluous O 2 − via its disproportionation in the chloroplast (Chen et al, 2018). Based on the results obtained for SOD activity and O 2 − production demonstrate that MaCDSP32 plays a key role in the regulation of ROS homeostasis by particularly targeting the SOD enzyme.…”
Section: Discussionmentioning
confidence: 91%
“…This result indicated that MaCDSP32 might affect the activity of chlorophyll-related enzymes under NaCl stress. Although NaCl treatment can increase the activity of chlorophyllase, the synthesis and degradation of chlorophyll are mainly affected by the activity of chlorophyll enzymes (Chen et al, 2018). This increased chlorophyllase activity might induce CDSP32 activity, which functions to protect photosynthetic system elements (Broin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is important for chloroplast biogenesis, and increases plant biological system capacity for abiotic stresses [61,62]. On the other hand, AAP6 is correlated with plant drought tolerance [63].…”
Section: Alsamman Et Al 2021mentioning
confidence: 99%
“…Abiotic stresses are nonbiological factors that influence living organisms in a specific environment that negatively affects the growth and yields of crop [3]. High salinity [2,4], drought [4,5], flooding [6,7], chilling [8][9][10], heat [4,10] and heavy metal stresses [11][12][13][14][15][16] are adverse natural factors that affect fruit tree growth and yield that are undesirable to be encountered during the whole process.…”
mentioning
confidence: 99%